Living Yoga : the Value of Yoga in Today's Life. - Saccidānanda, Svāmi (Routledge Library Editions: Yoga Ser., 2018)
The talks presented in this volume, first published in 1977, were originally delivered during a retreat in New York, in which speakers from a variety of spiritual traditions were represented. It aims to show the value of yoga in everyday life, and its relation to many other religions and philosophies.